GEN Z CLOTHING BRAND PREFERENCES: BANDWAGON EFFECT ON REGION OF CHINA CONSUMER - Goh, Venessa W.N. (2022)
When markets want to learn more about consumer choice behaviour, they must take brand preference into account. Brand preference has always been a great concern for major companies and markets. The research aim of this study is to determine the factors that will influence Chinese generation Z’s fast fashion clothing brand preference. This study proposes four different factors which are, the bandwagon effect, social media influencer, price, and brand image. Moreover, the study also examines whether bandwagon effect as a mediator will have positive influence between social media influencer and brand preference. The target population is Generation Z (10-25 years old) as they are the potential market consumers in this new digital era. The study applied a quantitative method by conducting a survey online in China and a total of 202 responses was received. After collecting data, the hypotheses generated were analysed using SPSS. Through the result of findings, bandwagon effect, social media influencer, price and brand image have a significant relationship with brand preference. It also confirmed that the role of bandwagon effect as a mediator will positively influence the relationship between social media influencer and brand preference. All hypotheses have been confirmed. The study mentioned the importance of businesses understanding China generation Z’s brand preference.